Impact of Climatic Elements on Winter Crop Productivity in Rangpur Area of Bangladesh - Azad, MAK; Hossain, MZ; Karmakar, S (Journal of Environmental Science and Natural Resources, 2015)
This study was carried out to identify the impact of climatic elements (temperature and rainfall) on winter crop productivity of HYV-boro, wheat and tomato in Rangpur area of Bangladesh. From regression analysis, an insignificant positive correlation between HYV boro productivity and winter rainfall was found during 1973-1990 and negative correlation during1991- 2008 period. For correlation between wheat productivity and winter rainfall, an insignificant positive relationship during 1973- 1990 and negative relationship during 1991-2008 was observed. The relationship between tomato productivity and winter rainfall was lower positive insignificant during 1973-1990 period and higher positive insignificant during 1991-2008 period. In the case of temperature, an insignificant negative correlation during 1973-1990 and positive correlation during 1991-2008 was found between HYV boro productivity and winter temperature. For wheat productivity, winter temperature showed significant negative correlation during 1973-1990 and insignificant positive correlation during 1991-2008. However, tomato productivity and winter temperature was positively insignificant during 1973-1990 and negatively insignificant during 1991-20008. From this study, it is concluded that the rainfall of recent period (1991-2008) was not suitable for boro and wheat but suitable for tomato. Similarly, temperature of the same period was favorable for boro and wheat but disfavorable for tomato in Rangpur area of Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22111 J. Environ. Sci. & Natural Resources, 6(2): 149-155 2013